Telocytes and Atrial Fibrillation: From Basic Research to Clinical Practice - V. I. Podzolkov; A. I. Tarzimanova; A. S. Frolova (Рациональная фармакотерапия в кардиологии)
The emergence of new research methods makes it possible to study the tissue, structural, cellular, and molecular causes of atrial fibrillation (AF). Recently, the role of interstitial telocyte cells in the pathogenesis of AF has been actively discussed. Telocytes are a special type of interstitial cells identified in many organs and tissues, including the heart. The roles of telocytes in the myocardium are diverse: they have pacemaker activity, and carry out structural and coordination communication between cells. The ability of these cells to change the speed of the electrical pulse in the atrial and ventricular myocardium has been proven. Telocytes form "atypical" connections with almost all types of cells in the human heart, which collects them in an integrated network. Using electron microscopy, it was found that interstitial cells have different types of connections in the network and can integrate "information" from the vascular and nervous systems, interstitial, immune system, stem cells, progenitor cells, and contractile cardiomyocytes. Currently, the results of studies have been obtained that prove both positive and negative effects of telocytes on the occurrence of various diseases of the cardiovascular system. The role of telocytes in AF arrhythmogenesis remains a subject of discussion. The unique properties of telocytes in providing intercellular contacts, transmitting genetic information, and their ability to regenerate heart tissue are undoubtedly the most promising areas of modern cardiology. There is evidence of both direct and indirect effects of telocytes on the electrophysiological properties of the myocardium. There is no doubt that the development of this area opens up new therapeutic targets for the prevention and treatment of AF.